SRM power density improvement utilising rotor conducting screens and DC‐link voltage boosting for EV applications - Aly A. Abdel‐Aziz; Khaled H. Ahmed; Ahmed M. Massoud; Barry W. Williams (IET Electrical Systems in Transportation)
Abstract The power density enhancement of a four‐phase switched reluctance motor using rotor conducting screens and DC‐link voltage boosting for electric vehicle applications is studied. The effect of conducting screen thickness and material electrical conductivity on current rise time, developed torque, and output power is studied. Different screen shapes are compared that elicit the optimum screen design by formulating a multi‐objective optimisation problem based on maximising the developed torque and efficiency and minimising added material weight. A double arm common switch converter with a DC‐link voltage‐boosting capacitors is deployed. The boosted voltage provided by the capacitors aids the winding current to rapidly build‐up; thus, increasing the motor base speed, whence power rating. Finite element analysis results confirm the SRM drive's effectiveness in increasing the motor base speed and improving the torque range; hence make the power capability of SRMs to be competitive with an equivalent volume permanent magnet synchronous motor.